Examining default urban-aspect-ratios and sky-view-factors to identify priorities for thermal-sensitive public space design in hot-summer Mediterranean climates: The Lisbon case. (December 2017) - Nouri, A. Santos; Costa, João Pedro; Matzarakis, A.
Abstract: This study evaluates Lisbon's bioclimatic risk factors, and how such microclimatic considerations can be transferred into priorities for thermal sensitive Public Space Design (PSD) during periods of accentuated thermal stimuli. The examination was structured into three sequential stages to address how the often lack of meteorological information can be overcome to assess pedestrian thermal comfort thresholds within specific morphological configurations within the historical district of the city. Firstly, through the application of the human-biometeorological model RayMan, the monthly variations of diurnal Physiologically Equivalent Temperature (PET) and corresponding Physiological Stress (PS) fluctuations were examined to obtain an overall comprehension of annual thermal bioclimate conditions within Lisbon. Secondly, diurnal variations were analysed in more detail through hourly oscillations for July in order to obtain an understanding of how thermal comfort thresholds were influenced during one of the hottest months of the year. Thirdly, such results was subsequently cross examined within the constructed default urban Aspect Ratios (AR) and Sky-View-Factors (SVF) within the SkyHelios model to evaluate concrete hourly PSD priority for urban canyons with diverse morphological compositions. Based upon the results obtained from the study, adaptations of the thermo-physiological index were tested/used, namely the modified PET (mPET), PET Load (PETL), and the cumulative PETL (cPETL) in order identifyT hermalA ttenuationP riorities (TAP) for PSD within concrete locations of the identified canyons during specific periods of the day. Highlights: Lisbon's annual, monthly and diurnal bioclimatic risk factors were examined. Bioclimatic conditions were examined within different default urban-aspect-ratios. Oscillations of bioclimatic conditions in each urban-aspect-ratio were identified. Public space design identified as tool to confront climatological aggravations. Urban thermal attenuation priorities were built from thermo-physiological indices.